2021
DOI: 10.3389/fonc.2021.756888
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells: Metabolic Characterization for Targeted Cancer Therapy

Abstract: The subpopulation of cancer stem cells (CSCs) within tumor bulk are known for tumor recurrence and metastasis. CSCs show intrinsic resistance to conventional therapies and phenotypic plasticity within the tumor, which make these a difficult target for conventional therapies. CSCs have different metabolic phenotypes based on their needs as compared to the bulk cancer cells. CSCs show metabolic plasticity and constantly alter their metabolic state between glycolysis and oxidative metabolism (OXPHOS) to adapt to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 190 publications
(223 reference statements)
1
12
0
Order By: Relevance
“…GSEA showed that the expression of the gene set involved in the oxidative phosphorylation (OXPHOS) pathway was ranked the highest in ALG1-, ALG2-, ALG6-, and ALG7-expression positive CSCs and the third highest in ALG12-expression positive CSCs (Figure 5A and 5B, and Supplementary Figure 2A-C). OXPHOS, the major source of adenosine triphosphate (ATP) in several cancer types, regardless of the increased aerobic glycolysis, plays a crucial role in tumorigenesis and tumor progression and addresses the energy demands of CSCs, including GSCs (30)(31)(32). Consistently, enrichment of the OXPHOS pathway in ALG-expression positive CSCs was veri ed by GESA using the GOBP and KEGG gene sets (Figure 5C and 5D, and Supplementary Figure 2D-F).…”
Section: Nand C-linked Glycosylation Pathways Are Associated With Ste...mentioning
confidence: 55%
See 1 more Smart Citation
“…GSEA showed that the expression of the gene set involved in the oxidative phosphorylation (OXPHOS) pathway was ranked the highest in ALG1-, ALG2-, ALG6-, and ALG7-expression positive CSCs and the third highest in ALG12-expression positive CSCs (Figure 5A and 5B, and Supplementary Figure 2A-C). OXPHOS, the major source of adenosine triphosphate (ATP) in several cancer types, regardless of the increased aerobic glycolysis, plays a crucial role in tumorigenesis and tumor progression and addresses the energy demands of CSCs, including GSCs (30)(31)(32). Consistently, enrichment of the OXPHOS pathway in ALG-expression positive CSCs was veri ed by GESA using the GOBP and KEGG gene sets (Figure 5C and 5D, and Supplementary Figure 2D-F).…”
Section: Nand C-linked Glycosylation Pathways Are Associated With Ste...mentioning
confidence: 55%
“…OXPHOS is a major source of ATP in several cancer types; however, aerobic glycolysis contributes to tumorigenesis and tumor progression (30). Several independent lines have indicated that OXPHOS plays a crucial role in addressing the energy demands of CSCs, including GSCs (31,32). Notably, GSEA showed that the gene sets involved in the mTORC1 and MYC pathways were enriched in all ALG enzyme family-expression positive CSCs (Figure 5 and Supplementary Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…CSCs exhibit metabolic flexibility, which enables them to adapt to changing nutrient availability and microenvironmental stresses [ 126 ]. CSCs have a unique metabolic phenotype that switches between glycolysis and oxidative phosphorylation (OXPHS) to adapt to nutrient deficiency and therapeutic stress [ 127 ]. The cholesterol biosynthesis pathway has recently been identified as crucial in the proliferation, survival, and differentiation of CSCs in TNBC [ 16 ].…”
Section: Therapies Targeting Cscs Plasticity In Tnbcmentioning
confidence: 99%
“…Metabolic heterogeneity in CSCs has been an ongoing field of intense research, as the lack of a common pattern makes their metabolic characterization a challenging matter. The above results highlight the fact that elucidation of the metabolic signatures of all CSC subpopulations in a tumor is mandatory for their effective eradication; targeting both OXPHOS and glycolysis may constitute a better therapeutic strategy against them [ 36 ].…”
Section: Cancer Stem Cell Metabolism—glycolysis or Oxidative Phosphor...mentioning
confidence: 99%
“…Lipid metabolism is dysregulated in cancer sustaining tumor growth, progression, and metastasis [ 49 ]. Increasing evidence reveals that lipid metabolism is also associated with the stemness properties of CSCs, which rely heavily on de novo lipogenesis and lipid oxidation, as indicated by the upregulation of key enzymes of these processes [ 36 ].…”
Section: Other Metabolic Pathways In Cscsmentioning
confidence: 99%